PERAN ORGANISASI PRISMA (PEMUDA REMAJA ISLAM MASJID) DALAM MENINGKATKAN PARTISIPASI KEGIATAN KEAGAMAAN DI MASYARAKAT CUGENANG - Basir, Abdul; Lutfiah, Lintang Puspita; Nurhasanah, Yusin Elsa (LPPM STAI Al-Azhary Cianjur, 2022)
The purpose of this research is to describe the role of PRISMA, the role of PRISMA in prospering the mosque, the role in fostering Muslim youth, the role in the participation of Islamic holiday celebrations, the role in supporting the Ta'mir of the mosque, the role in socializing the community. In this research, the writer uses descriptive qualitative method and for data collection using observation and interview methods. And the subject of this research is PRISMA Bahrul Huda. Based on research, the role of PRISMA Bahrul Huda in an effort to increase community participation is not only in the prosperity of the mosque but also a forum for youth to mobilize programs that have been planned in the social field. The community is very supportive of the programs organized by PRISMA Bahrul Huda, one of which is a program in the social field, namely Donations for Orphans, PRISMA plays a very important role in these activities. From these activities, orphans in Cibulakan village received more attention. With the establishment of the PRISMA Organization, the youth in this village are more focused on good and useful activities, although not all teenagers are yet, but with PRISMA Bahrul Huda this can minimize teenagers from bad activities.